The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1158/1078-0432.ccr-11-2513
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cocaine- and Amphetamine-Regulated Transcript Is Associated with Worse Survival in Small Bowel Carcinoid Tumors

Abstract: Purpose: Cocaine-and amphetamine-regulated transcript (CART) peptide exerts several regulatory functions acting both as neurotransmitter and hormone. We recently showed that CART is expressed in various neuroendocrine tumors, including small bowel carcinoids. The main objective of the present study was to examine whether CART expression is associated with survival in patients with small bowel carcinoid. Secondary aims were to assess whether CART expression is associated with other tumor characteristics or clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
2
20
1
Order By: Relevance
“…Specificity of CART antibodies (Cocalico, Reamstown, PA) was verified in CART-/-mice and with pre-absorption with CART55-102 [23]. 30-mer oligodeoxyribonucleotide probes for CART mRNA were used for in situ hybridization (ISH) in human [24] and rat [12] specimens as detailed [25].…”
Section: Immunocytochemistry In Situ Hybridization and Image Analysismentioning
confidence: 99%
“…Specificity of CART antibodies (Cocalico, Reamstown, PA) was verified in CART-/-mice and with pre-absorption with CART55-102 [23]. 30-mer oligodeoxyribonucleotide probes for CART mRNA were used for in situ hybridization (ISH) in human [24] and rat [12] specimens as detailed [25].…”
Section: Immunocytochemistry In Situ Hybridization and Image Analysismentioning
confidence: 99%
“…Tissues were collected at sacrifice 20 days postoperatively and processed as previously described (12). Antibodies are presented in Table 1.…”
Section: Plasma Analysesmentioning
confidence: 99%
“…Changes in CART expression in the enteric nervous system in pathological states have not been the subject of extensive research and to the best of our knowledge have been investigated only in humans and domestic pigs. It has been demonstrated that inflammatory states affect the number of CART-positive nerve fibres (Gunnarsdottir et al 2007;Gonkowski et al 2009b) and that CART expression is correlated with prognosis in small intestinal carcinoid tumours in humans (Landerholm et al 2012). However, the role of CART in canine IBD has not been studied to date.…”
mentioning
confidence: 99%